A Prospective Obsevational Study On Adnexal Masses -Comparison Of Clinical Impression, Ca -125, Ultrasound Findings And Histopathological Diagnosis (East West Medical College Journal, 2025)
Adnexal mass may be found in women of all ages with  a prevalence of 1:1000 in premenopausal  group and  3:1000 in post menopausal group.  The risk of malignancy  increases  with age. The current study was carried out in  the department of Obstetrics and Gynaecology   in  Ad-din Women’s   Medical College Hospital, Maghbazar, Dhaka from Ist July 2023 to 30 th  June 2024. It was a hospital based observational study which included 100 patients of adnexal masses who required surgery. The goal of the study was  to compare sensitivity , specificity , predictive value of clinical evaluation , USG with colour Doppler, CA-125 ,RMI score and to compare them with histopatholoy.  All cases were evaluated clinically, by Ultrasonogram with colour doppler ,CA-125  and RMI score. After surgery specimens were sent for histopathology and reports were compared with pre surgical evaluation. 93% cases were of ovarian origin and 7%  were  non ovarian  cases. Histopathology  reports showed that 68%  adnexal  masses  were benign and 32% were malignant. The principle tool  for evaluation of adnexal mass was Ultrasonogram with colour doppler which had the highest diagnostic accuracy(92%) . But clinical evaluation had the highest sensitivity(90.62%) and  RMI score had the highest specificity(95.59%) .With these comparatively simple  methods we can  diagnose adnexal masses without expensive advanced imaging modalities.EWMCJ Vol. 13, No. 2, July 2025: 143-148